High-strength and high-toughness PC / ABS composite material as well as preparation method and application thereof
SEBS-g-MAH graft copolymer prepared through Co60 radiation technology significantly improves the toughness and heat resistance of PC/ABS composite materials, solves the limitations of traditional materials in terms of toughness and heat resistance, and meets the new energy vehicles and High performance requirements for electronic devices.
Patent Information
- Application Number
- CN202411567176.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-05
- Publication Date
- 2025-01-10
AI Technical Summary
Traditional PC/ABS composites have limitations in toughness, compatibility and heat resistance, and it is difficult to meet high-performance needs such as new energy vehicles.
SEBS-g-MAH graft copolymer is prepared through Co60 radiation technology and applied to PC/ABS composite materials to form high-strength and high-toughness composite materials, improve the compatibility and microstructure of the material, and enhance its toughness and impact strength. and heat resistance.
Without sacrificing processing performance, the toughness, impact strength and heat resistance of the material are significantly improved, and the application requirements of high-performance requirements such as new energy vehicles and electronic equipment shells are met, demonstrating excellent mechanical properties and thermal stability .
Smart Images

Figure BDA0005119550300000121 
Figure BDA0005119550300000131
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polymer composite materials, and specifically relates to a high-strength and high-toughness PC / ABS composite material and a preparation method and application thereof. Background Art
[0002] PC / ABS composites have become key materials in the automotive, electronics and electrical appliance industries due to their excellent mechanical properties, heat resistance and processing convenience. However, as industrial applications have increased requirements for material performance, the limitations of traditional PC / ABS composites in toughness, compatibility and heat resistance have gradually become a bottleneck restricting their further application.
[0003] In traditional PC / ABS composite materials, toughness, compatibility and heat resistance are achieved through specific formulations and processing techniques. For example, application number: CN201310558974.4 discloses an ABS composite PC material alloy, which can balance the toughness and hardness of the material by adjusting the mixing ratio of PC and ABS. In addition, the addition of compatibilizers such as maleic anhydride grafting or methyl methacrylate grafting can improve the compatibility of the two phases, thereby improving the overall performance of the material. In addition, long-term use of PC / ABS composites at high temperatures may lead to performance degradation, especially in terms of heat resistance. PC / ABS is usually not as good as pure PC. Researchers such as Andrzejewski, Jacek et.al Development of hybrid composites reinforced with biocarbon / carbon fiber system. The comparative study for PC, ABS and PC / ABS based materials, reinforced PC / ABS composites by adding biocarbon / carbon fiber system to improve their toughness and heat resistance.
[0004] With the rapid development of new energy vehicles in recent years, people have higher requirements on the performance of PC / ABS materials, and the toughness, impact strength and heat resistance of PC / ABS composite materials need to be improved. Summary of the invention
[0005] In order to solve the above problems, the present invention provides a high-strength and high-toughness PC / ABS composite material and its preparation method and application. SEBS-g-MAH graft copolymer is prepared by Co60 radiation technology and applied to PC / ABS composite material. Co60 radiation is an efficient and environmentally friendly method for initiating polymerization reaction, which can evenly generate free radicals on the hydrogenated styrene-ethylene-butadiene-styrene molecular chain, thereby initiating the polymerization of maleic anhydride to form evenly distributed graft chains. This uniform graft structure not only improves the compatibility of the material, but also significantly improves the microstructure of the material, thereby significantly improving the toughness, impact strength and heat resistance of the material without sacrificing processing performance.
[0006] The present invention solves the above technical problems through the following technical solutions.
[0007] The first object of the present invention is to provide a high-strength and high-toughness PC / ABS composite material, which is prepared from the following components in parts by weight: 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of a compatibilizer, and 0.1 to 1 part of an antioxidant.
[0008] The compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene as raw materials, and a polymerization reaction is carried out by Co60 gamma ray radiation to form a SEBS-g-MAH grafted product.
[0009] Furthermore, the preparation method of the SEBS-g-MAH grafted material comprises the following steps:
[0010] Maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene are melt mixed to form a mixture.
[0011] The mixture is placed in Co60 gamma rays for irradiation, with an absorbed dose of 30 kGy to 100 kGy, and hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride are polymerized to form SEBS-g-MAH grafts.
[0012] Furthermore, the mass ratio of the hydrogenated styrene-ethylene-butadiene-styrene to maleic anhydride is 15-25:3-6.
[0013] Furthermore, the temperature of the melt mixing is 150° C. to 170° C., and the mixing time is 3 min to 10 min.
[0014] Furthermore, the antioxidant is a mixture of hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:1.
[0015] Furthermore, the polycarbonate resin has a melt flow rate of 5 g / 10 min to 10 g / 10 min, and a relative molecular mass of 30,000 g / mol to 40,000 g / mol.
[0016] Furthermore, the melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15 g / 10 min to 25 g / 10 min, and the relative molecular mass is 100,000 g / mol to 150,000 g / mol.
[0017] A second object of the present invention is to provide a method for preparing the above-mentioned high-strength and high-toughness PC / ABS composite material, comprising the following steps:
[0018] The polycarbonate resin and the acrylonitrile-butadiene-styrene copolymer resin are dried at 80° C. to 100° C. for 2 h to 6 h and set aside.
[0019] Weigh each component according to mass proportion, including 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of compatibilizer, and 0.1 to 1 part of antioxidant, mix well, and obtain a mixture.
[0020] The mixed material is put into an extrusion granulator, melt-extruded at 180°C to 270°C, cooled and pelletized to obtain a high-strength and high-toughness PC / ABS composite material.
[0021] Furthermore, the temperature settings of each zone of the extrusion granulator are 180℃~270℃ for zone 1, 180℃~270℃ for zone 2, 180℃~270℃ for zone 3, 220℃~280℃ for zone 4, 220℃~270℃ for zone 5, 220℃~270℃ for zone 6, 220℃~270℃ for zone 7, 220℃~270℃ for zone 8, 220℃~270℃ for zone 9, 220℃~270℃ for zone 10, and 220℃~270℃ for zone 11, and the extrusion speed is 200r / min~600r / min.
[0022] The third object of the present invention is to provide the above-mentioned high-strength and high-toughness PC / ABS composite material for use in preparing charging pile housings or electronic equipment housings.
[0023] Compared with the prior art, the present invention has the following beneficial effects:
[0024] (1) The compatibilizer of the present invention uses maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene as raw materials, and undergoes polymerization reaction after Co60γ-ray radiation to form SEBS-g-MAH grafts. After hydrogenated styrene-ethylene-butadiene-styrene is irradiated with Co60γ-rays, styrene groups on the molecular chain uniformly generate free radicals, and these free radicals trigger the polymerization reaction of maleic anhydride to form a uniformly distributed graft chain structure, which not only improves the compatibility of the material, but also significantly improves the microstructure of the material, so that it can be applied to PC / ABS composite materials without sacrificing processing performance. Since the grafted chains of SEBS-g-MAH form chemical bonds with the PC resin matrix and the ABS resin matrix, the compatibility between the two is effectively improved, the discontinuity of the interface phase is reduced, and the toughness, impact strength and heat resistance of the material are improved.
[0025] (2) The heat resistance of SEBS-g-MAH in the SEBS-g-MAH grafted product used in the present invention improves the thermal stability of the composite material, so that it can still maintain excellent mechanical properties under high temperature environment. In addition, due to the mild conditions of the radiation-induced polymerization reaction, the processing performance of the composite material is guaranteed, meeting the industry's high requirements for material processing convenience and molding efficiency.
[0026] (3) The present invention optimizes the ratio and processing conditions of PC, ABS, SEBS-g-MAH grafts and antioxidants and other additives, showing significant advantages in mechanical properties, heat resistance, processing performance and environmental friendliness. It is expected to play an important role in high-performance application fields such as new energy vehicle charging piles and electronic equipment housings, meeting the urgent needs of modern industry for high-performance materials. With further research and development, this material is expected to become an important force in promoting the development of materials science. DETAILED DESCRIPTION
[0027] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0028] It should be noted that the professional terms used in the present invention are only for the purpose of describing specific embodiments and are not intended to limit the scope of protection of the present invention. Unless otherwise specifically stated, the various raw materials, reagents, instruments and equipment used in the following embodiments of the present invention can be purchased from the market or prepared by existing methods.
[0029] Prior art, such as application number: CN201310558974.4, discloses an ABS composite PC material alloy. By adjusting the mixing ratio of PC and ABS, the toughness and hardness of the material can be balanced. In addition, the addition of compatibilizers such as maleic anhydride grafting or methyl methacrylate grafting can improve the compatibility of the two phases, thereby improving the overall performance of the material. In addition, long-term use of PC / ABS composites at high temperatures may lead to performance degradation, especially in terms of heat resistance. PC / ABS is usually not as good as pure PC. Researchers such as Andrzejewski, Jacek et.al Development of hybrid composites reinforced with biocarbon / carbon fiber system. The comparative study for PC, ABS and PC / ABS based materials, reinforced PC / ABS composites by adding biocarbon / carbon fiber system to improve their toughness and heat resistance.
[0030] With the rapid development of new energy vehicles in recent years, people have higher requirements on the performance of PC / ABS materials, and the toughness, impact strength and heat resistance of PC / ABS composite materials need to be improved.
[0031] Based on the above problems, the present invention provides a high-strength and high-toughness PC / ABS composite material, which is prepared from the following components in parts by weight: 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of a compatibilizer, and 0.1 to 1 part of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene as raw materials, and a polymerization reaction is carried out under Co60γ-ray radiation to form a SEBS-g-MAH graft.
[0032] The compatibilizer of the invention uses maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene as raw materials, performs polymerization reaction after Co60γ-ray radiation, and forms SEBS-g-MAH grafted products. After the hydrogenated styrene-ethylene-butadiene-styrene is irradiated with Co60γ-rays, styrene groups on the molecular chain uniformly generate free radicals, and the free radicals trigger the polymerization reaction of maleic anhydride to form a uniformly distributed graft chain structure, which not only improves the compatibility of the material, but also significantly improves the microstructure of the material, so that the compatibility is applied to PC / ABS composite materials without sacrificing processing performance. Since the grafted chains of SEBS-g-MAH form chemical bonds with PC resin matrix and ABS resin matrix, the compatibility between the two is effectively improved, the discontinuity of the interface phase is reduced, and the toughness, impact strength and heat resistance of the material are improved, thereby solving the problems of the existing PC / ABS materials in terms of toughness, impact strength and heat resistance caused by the discontinuity of compatibility.
[0033] The present invention optimizes the ratio and processing conditions of PC, ABS, SEBS-g-MAH grafts, antioxidants and other additives. The ratio has good processability, provides excellent mechanical properties, reduces costs, improves material economy, and shows significant advantages in mechanical properties, heat resistance, processing performance and environmental friendliness.
[0034] In one embodiment, the preparation method of the SEBS-g-MAH grafted material comprises the following steps:
[0035] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 15-25:3-6 at 150° C.-170° C. for 3 min-10 min to form a mixture.
[0036] S2. The mixture is irradiated with Co60 gamma rays with an absorbed dose of 30 kGy to 100 kGy, and hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride are polymerized to form SEBS-g-MAH grafts.
[0037] Co60 radiation is an efficient and environmentally friendly method for initiating polymerization reactions. It can break the molecular chain of hydrogenated styrene-ethylene-butadiene-styrene, generate free radicals evenly on the internal molecular chain, and then initiate the polymerization of maleic anhydride to form evenly distributed graft chains. The molecular formula of SEBS-g-MAH grafted product is: SEBS-g-[C=CH-CH=CH-C(=O)OH] n , n represents the degree of polymerization, where n is 800-2400. During the radiation process, MAH will also undergo autonomous polymerization to form non-grafted polymaleic anhydride, which can be expressed as: [C=CH-CH=CH-C(=O)OH] m, m represents the degree of polymerization, where m is 60-600. Compared with the traditional mechanical blending method, radiation grafting technology can achieve chemical bonding between different components at the molecular level, significantly improving the compatibility and comprehensive performance of the material. Radiation grafting not only improves the compatibility of SEBS with PC / ABS matrix, but also introduces additional chemical bonds through chemical reactions, enhancing the toughness and impact resistance of the material. It not only improves the compatibility of the material, but also significantly improves the microstructure of the material. The radiation-grafted SEBS-g-MAH graft has good stability at high temperatures, allowing the final material to maintain its performance in harsh use environments, thereby significantly improving the toughness, impact strength and heat resistance of the material without sacrificing processing performance.
[0038] In one embodiment, the antioxidant is a hindered phenol antioxidant 1010 and a phosphite antioxidant 168. The hindered phenol antioxidant 1010 and the phosphite antioxidant 168 are mixed in a mass ratio of 1:1. The antioxidant protects the stability of the material during high temperature processing and long-term use.
[0039] In one embodiment, the polycarbonate resin has a melt flow rate of 5 g / 10 min to 10 g / 10 min and a relative molecular mass of 30,000 g / mol to 40,000 g / mol, providing basic strength and heat resistance of the composite material.
[0040] In one embodiment, the melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15 g / 10 min to 25 g / 10 min, and the relative molecular mass is 100,000 g / mol to 150,000 g / mol, which gives the composite material good processability and toughness.
[0041] In addition, the present invention provides a method for preparing the above-mentioned high-strength and high-toughness PC / ABS composite material, comprising the following steps:
[0042] The polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin are dried at 80°C to 100°C for 2h to 6h to remove moisture to avoid bubbles or pores during processing. Vacuum drying or other drying methods can also be used to remove moisture or other volatile substances in PC and ABS resins for later use.
[0043] Weigh each component according to mass proportion, including 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of compatibilizer, and 0.1 to 1 part of antioxidant, put them into a high-speed mixer and mix them thoroughly until a uniform mixture is formed.
[0044] The mixed material is put into an extrusion granulator, melt-extruded at 180°C to 270°C, cooled and pelletized to obtain a high-strength and high-toughness PC / ABS composite material.
[0045] In melt extrusion, a single-screw or twin-screw extruder can be used to adapt to different production scales and efficiency requirements; in the cooling and pelletizing process, water cooling or air cooling can be used to adapt to different production environments.
[0046] During the melt mixing process, SEBS-g-MAH grafts form chemical bonds with PC and ABS at the molecular level, effectively improving the compatibility between the two, reducing the discontinuity of the interface phase, and significantly improving the compatibility and mechanical properties of the material. The ungrafted MAH groups react with PC to form chemical bonds, further improving the mechanical strength and toughness of the material. While maintaining processing convenience, the prepared PC / ABS composite material exhibits excellent impact resistance and heat resistance.
[0047] Furthermore, the temperature settings of each zone of the extrusion granulator are 180℃~270℃ for zone 1, 180℃~270℃ for zone 2, 180℃~270℃ for zone 3, 220℃~280℃ for zone 4, 220℃~270℃ for zone 5, 220℃~270℃ for zone 6, 220℃~270℃ for zone 7, 220℃~270℃ for zone 8, 220℃~270℃ for zone 9, 220℃~270℃ for zone 10, and 220℃~270℃ for zone 11, and the extrusion speed is 200r / min~600r / min.
[0048] The present invention also provides the use of the above-mentioned high-strength and high-toughness PC / ABS composite material in the preparation of charging pile shells or electronic equipment shells. In the application of charging piles, the PC / ABS composite material of the present invention exhibits excellent impact resistance and heat resistance, and can effectively prevent the material from being deformed or damaged due to high temperature or mechanical stress, thereby extending the service life of the charging pile. In addition, the material also exhibits excellent comprehensive performance in the field of electronic equipment shells, and is suitable for high-end electronic products that require high durability and thermal stability.
[0049] The invention is further described below through specific examples.
[0050] Example 1
[0051] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene, and undergoes polymerization reaction under Co60 gamma ray radiation to form a SEBS-g-MAH graft.
[0052] The preparation method of SEBS-g-MAH grafted material comprises the following steps:
[0053] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 20:5 at 150° C. for 5 minutes to form a mixture.
[0054] S2. Place the mixture in a Co60 gamma ray radiation field to receive 50 kGy of gamma ray radiation to form a SEBS-g-MAH graft.
[0055] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0056] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0057] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0058] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0059] Example 2
[0060] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene, and undergoes polymerization reaction under Co60 gamma ray radiation to form a SEBS-g-MAH graft.
[0061] The preparation method of SEBS-g-MAH grafted material comprises the following steps:
[0062] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 25:3 at 150° C. for 5 minutes to form a mixture.
[0063] S2. Place the mixture in a Co60 gamma ray radiation field to receive 70 kGy of gamma ray radiation to form a SEBS-g-MAH graft.
[0064] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0065] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0066] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0067] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0068] Example 3
[0069] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene, and undergoes polymerization reaction under Co60 gamma ray radiation to form a SEBS-g-MAH graft.
[0070] The preparation method of SEBS-g-MAH grafted material comprises the following steps:
[0071] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 15:6 at 150° C. for 5 minutes to form a mixture.
[0072] S2. Place the mixture in a Co60 gamma ray radiation field to receive 100 kGy of gamma ray radiation to form a SEBS-g-MAH graft.
[0073] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0074] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0075] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0076] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0077] Embodiment 4:
[0078] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 75 parts of polycarbonate resin, 25 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene, and undergoes polymerization reaction under Co60 gamma ray radiation to form a SEBS-g-MAH graft.
[0079] The preparation method of SEBS-g-MAH grafted material comprises the following steps:
[0080] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 20:5 at 150° C. for 5 minutes to form a mixture.
[0081] S2. Place the mixture in a Co60 gamma ray radiation field to receive 50 kGy of gamma ray radiation to form a SEBS-g-MAH graft.
[0082] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0083] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0084] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0085] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0086] Embodiment 5:
[0087] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 8 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene, and undergoes polymerization reaction under Co60 gamma ray radiation to form a SEBS-g-MAH graft.
[0088] The preparation method of SEBS-g-MAH grafted material comprises the following steps:
[0089] S1. Melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at a mass ratio of 20:5 at 150° C. for 5 minutes to form a mixture.
[0090] S2. Place the mixture in a Co60 gamma ray radiation field to receive 50 kGy of gamma ray radiation to form a SEBS-g-MAH graft.
[0091] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0092] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0093] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0094] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0095] Comparative Example 1
[0096] A high-strength and high-toughness PC / ABS composite material is prepared from the following components in parts by mass: 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of a compatibilizer, and 0.5 parts of an antioxidant; wherein the compatibilizer is commercially available SEBS-g-MAH.
[0097] The preparation method of the above-mentioned high-strength and high-toughness PC / ABS composite material comprises the following steps:
[0098] Step 1: Dry the polycarbonate resin and acrylonitrile-butadiene-styrene copolymer resin at 100° C. for 4 hours to remove moisture to avoid bubbles or pores during processing, and set aside.
[0099] Step 2, weigh each component according to mass fraction, 85 parts of polycarbonate resin, 15 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 parts of compatibilizer, and 0.5 parts of antioxidant, put them into a high-speed mixer and mix them thoroughly for 5 minutes to form a uniform mixture.
[0100] Step 3, putting the mixed material into a twin-screw extruder for melt extrusion, the temperature settings of each zone of the twin-screw extruder are respectively 220°C for zone 1, 230°C for zone 2, 235°C for zone 3, 250°C for zone 4, 250°C for zone 5, 260°C for zone 6, 265°C for zone 7, 265°C for zone 8, 255°C for zone 9, 250°C for zone 10, and 250°C for zone 11, the screw speed is 240r / min, and after extrusion, high-strength and high-toughness PC / ABS composite material particles are obtained through cooling and pelletizing.
[0101] The properties of the PC / ABS composite material particles prepared in Examples 1 to 5 and Comparative Example 1 were tested, wherein the tensile properties were tested according to GB1040-92, the bending properties were tested according to GB / T9341-2000, and the impact properties were tested according to GB / T1843-2008. The results are shown in Table 1.
[0102] Table 1 Mechanical properties of PC / ABS composite materials prepared in Example 1 to Example 5 and Comparative Example 1
[0103]
[0104]
[0105] As shown in Table 1, the present invention uses radiation grafting technology to melt-mix hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride at high temperature, and then under Co60γ-ray radiation, the styrene groups on the hydrogenated styrene-ethylene-butadiene-styrene molecular chain generate free radicals, and these free radicals initiate the polymerization of maleic anhydride to form SEBS-g-MAH grafts. This graft forms chemical bonds with PC and ABS at the molecular level, significantly improving the compatibility and mechanical properties of the material. The MAH group that has not been grafted reacts with PC to form a chemical bond, further improving the mechanical strength and toughness of the material. The tensile bending strength in the embodiment is higher than that of the comparative example, indicating that the SEBS-g-MAH graft prepared by radiation is better than the ordinary commercially available SEBS-g-MAH.
[0106] Increasing the ABS content in Example 4 and increasing the compatibilizer content in Example 5 can improve the elongation at break of the material, while the strength and impact strength of the material are significantly reduced. However, the strength of the PC / ABS material is the key, and the change in elongation at break can be ignored.
[0107] Radiation grafting technology not only enhances the physical properties of the material, but also improves the stability of the material in high temperature environments, allowing the composite material to maintain its performance under more stringent conditions of use.
[0108] The composite materials prepared by radiation grafting technology have significantly improved tensile strength, elongation at break, flexural strength, fracture strength and impact strength, showing excellent mechanical properties. At the same time, the thermal stability of the material has also been improved, enabling it to maintain its performance in high temperature environments.
[0109] This high-strength and high-toughness PC / ABS composite material is particularly suitable for applications with high material performance requirements, such as new energy vehicle charging piles, electronic equipment housings, etc. Its excellent mechanical properties, heat resistance and processing convenience are expected to play an important role in the field of high-performance engineering plastics and promote the development of related industries.
[0110] It should be noted that when the present invention involves a numerical range, it should be understood that the two endpoints of each numerical range and any value between the two endpoints can be selected. Since the steps and methods used are the same as those in the embodiments, in order to avoid redundancy, the present invention describes a preferred embodiment. Although the preferred embodiments of the present invention have been described, those skilled in the art may make additional changes and modifications to these embodiments once they know the basic creative concept. Therefore, the attached claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0111] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A high-strength and high-toughness PC / ABS composite material, characterized in that: The invention is prepared from the following components in parts by weight: 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of compatibilizer, and 0.1 to 1 part of antioxidant; The compatibilizer is made of maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene as raw materials, and a polymerization reaction is carried out by Co60 gamma ray radiation to form a SEBS-g-MAH grafted product.
2. The high-strength and high-toughness PC / ABS composite material according to claim 1, characterized in that: The preparation method of the SEBS-g-MAH grafted material comprises the following steps: maleic anhydride and hydrogenated styrene-ethylene-butadiene-styrene are melt-mixed to form a mixture; The mixture is placed in Co60 gamma rays for irradiation, with an absorbed dose of 30 kGy to 100 kGy, and hydrogenated styrene-ethylene-butadiene-styrene and maleic anhydride are polymerized to form SEBS-g-MAH grafts.
3. The high-strength and high-toughness PC / ABS composite material according to claim 2, characterized in that: The mass ratio of the hydrogenated styrene-ethylene-butadiene-styrene to maleic anhydride is 15-25:3-6.
4. The high-strength and high-toughness PC / ABS composite material according to claim 2, characterized in that: The temperature of the melt mixing is 150° C. to 170° C., and the mixing time is 3 min to 10 min.
5. The high-strength and high-toughness PC / ABS composite material according to claim 1, characterized in that: The antioxidant is a mixture of hindered phenol antioxidant 1010 and phosphite antioxidant 168 in a mass ratio of 1:
1.
6. The high-strength and high-toughness PC / ABS composite material according to claim 1, characterized in that: The polycarbonate resin has a melt flow rate of 5 g / 10 min to 10 g / 10 min, and a relative molecular mass of 30000 g / mol to 40000 g / mol.
7. The high-strength and high-toughness PC / ABS composite material according to claim 1, characterized in that: The melt flow rate of the acrylonitrile-butadiene-styrene copolymer resin is 15 g / 10 min to 25 g / 10 min, and the relative molecular mass is 100000 g / mol to 150000 g / mol.
8. A method for preparing the high-strength and high-toughness PC / ABS composite material according to any one of claims 1 to 7, characterized in that: The following steps are involved: The polycarbonate resin and the acrylonitrile-butadiene-styrene copolymer resin are dried at 80° C. to 100° C. for 2 h to 6 h and set aside; Weigh each component according to mass proportion, including 60 to 95 parts of polycarbonate resin, 5 to 40 parts of acrylonitrile-butadiene-styrene copolymer resin, 5 to 20 parts of compatibilizer, and 0.1 to 1 part of antioxidant, and mix them evenly to obtain a mixture; The mixed material is put into an extrusion granulator, melt-extruded at 180°C to 270°C, cooled and pelletized to obtain a high-strength and high-toughness PC / ABS composite material.
9. The method for preparing the high-strength and high-toughness PC / ABS composite material according to claim 8, characterized in that: The temperature settings of each zone of the extrusion granulator are as follows: zone 1 temperature 180℃~270℃, zone 2 temperature 180℃~270℃, zone 3 temperature 180℃~270℃, zone 4 temperature 220℃~280℃, zone 5 temperature 220℃~270℃, zone 6 temperature 220℃~270℃, zone 7 temperature 220℃~270℃, zone 8 temperature 220℃~270℃, zone 9 temperature 220℃~270℃, zone 10 temperature 220℃~270℃, zone 11 temperature 220℃~270℃, and the extrusion speed is 200r / min~600r / min.
10. Use of the high-strength and high-toughness PC / ABS composite material according to any one of claims 1 to 7 in preparing a charging pile housing or an electronic device housing.
Citation Information
Patent Citations
ABS (acrylonitrile butadiene styrene) compounded PC (polycarbonate) material alloy
CN103602030A